Elucidation of procoagulant mechanism and pathophysiological significance of a new prothrombin activating metalloprotease purified from Daboia russelii russelii venom. (15th June 2015) - Thakur, Rupamoni; Chattopadhyay, Pronobesh; Ghosh, Siddharth S.; Mukherjee, Ashis K.
Abstract: The procoagulant proteases present in Russell's Viper venom (RVV) are responsible for promoting consumption coagulopathy in victims. In this study, a procoagulant metalloprotease (Rusviprotease) possessing prothrombin activating and α-fibrinogenase properties has been purified and characterized from RVV. Rusviprotease is a 26.8 kDa glycoprotein which also exists in other multimeric forms. The peptide mass fingerprinting and secondary structure analyses of Rusviprotease revealed its similarity with snake venom prothrombin activators and metalloproteases. Similar to group A prothrombin activators, Rusviprotease cleaved prothrombin independent of any co-factor requirement generating meizothrombin which is further cleaved to form thrombin. The Km and Vmax values of Rusviprotease towards prothrombin were determined to be 1.73 μM, and 153.5 nM thrombin generated/min/μmoles of Rusviprotease, respectively. The Km and Vmax values of Rusviprotease towards fibrinogen were calculated to be 3.14 μM and 78.7 nmol/min, respectively. Spectrofluorometric study provided the evidence of interaction between Rusviprotease and factor Xa with a Kd value of 6.64 nM. This interaction augmented the prothrombin activating property of the factor Xa-prothrombinase-Rusviprotease complex by 2.5 fold. Intravenous injection of Rusviprotease to BALB/c mice (0.1 mg/kg) resulted in in vivo defibrinogenation rendering the blood incoagulable. In conclusion, Rusviprotease is the first example of a prothrombin activator with fibrinogenolytic property purified from Daboia russelii russelii venom. Highlights: Rusviprotease is a 26.8 kDa multimeric procoagulant melatolloprotease from RVV. Rusviprotease is the first report of a prothrombin activator from RVV. Rusviprotease belongs to the family of Group A-prothrombin activators. Rusviprotease exhibits concentration-dependent platelet aggregation and disaggregation. Rusviprotease demonstrates in vivo defibrinogenation in experimental mice.